Contextual transposition: Didactic strategy for the writing of the argumentative essay (Revista Torreón Universitario, 2022)
The objective of this educational research was to assess the impact of the didactic strategy "contextual transposition" in the writing of argumentative essays. This strategy is located in the sociocultural approach of textual production and emerges as an innovation in the diagnostic stage of this research. Four phases were defined for its application: a) sensitization, b) exploration and discussion, c) transposition and, d) evaluation. This is participatory action research, which was applied to tenth grade “A” students of the Benito Salinas de Dolores-Carazo Institute in Nicaragua, during the second semester of 2020. The research instruments were the diagnostic test, the didactic unit, the final test, the evaluation rubric of the essay written by the students, and the field journal. The main results are that from the contextual transposition, the students improved the written production, the definition of the thesis, and the organization of the ideas and structure of the essay, however, its impact on the reproduction of the sociocultural context or image of The reality of the student at the dialogic text level is limited, therefore, more studies must be carried out to understand and overcome the limitations.
Keywords: Argumentation; sociocultural approach; central idea; written production; dialogic text; contextual transposition